دور العلاقة التّكامليّة بين حوكمة الشّركات والرّقابة الدّاخلية في تحسين الأداء المالي لشركة البوتاس العربية بالأردن - شويرفي، هاجر; قازوز، رفيقة (جامعة الوادي University of Eloued, 2025)
نهدف من خلال دراستنا إلى التّطرق لممارسات الحوكمة وإجراءات الرّقابة الدّاخلية لدى شركة البوتاس العربية بالأردن وأثرها على الأداء المالي، خلال الفترة الزّمنية الممتدّة من سنة 2019 لغاية 2023، ودراسة العلاقة التّفاعلية والتّكاملية بينهما، بما يضمن الأداء الاقتصادي والمالي الجيّد. في هذا السّياق، تمّ الاعتماد على المنهج الوصفي والمنهج التّحليلي لعرض متغيّرات الدّراسة وتحليل العلاقة بينها، في الجانب النّظري، ثمّ منهج دراسة الحالة في الجانب التّطبيقي معتمدين على البيانات الرّسمية للشّركة وتقاريرها السّنوية. وتوصّلنا إلى أن الشّركة تلتزم بتحقيق الشّفافية والمصداقية في عرض وإعداد القوائم المالية، خدمة لمصالحها ومصالح الأطراف المتفاعلة معها، إلى جانب البيئة الرّقابية المحكمة الّتي تساعد على إدارة المخاطر بمرونة، وتعظيم الأرباح واتّخاذ القرارات بكفاءة Through our study, we aim to address the governance practices and internal control procedures of the Arab Potash Company in Jordan and their impact on financial performance, during the period from 2019 to 2023, and to study the interactive and complementary relationship between them, ensuring good economic and financial performance. In this context, we relied on the descriptive and analytical approaches to present the study variables and analyze the relationship between them, in the theoretical aspect, and then the case study approach in the practical aspect, relying on the company's official data and annual reports. We concluded that the company is committed to achieving transparency and credibility in presenting and preparing financial statements, serving its interests and those of the parties interacting with it, in addition to a tight regulatory environment that helps manage risks flexibly, maximize profits and make decisions efficiently.
The Role of the Complementary Relationship Between Corporate Governance and Internal Control in Improving the Financial Performance of the Arab Potash Company in Jordan - A Case Study for the period 2019-2023 -
مقال
Keywords: حوكمة الشّركات; الرّقابة الدّاخلية; القوائم المالية; الأداء المالي; Corporate Governance; Internal Control; Financial Statements; Financial Performance